Capital Intensity, Deferred Tax Expense, Company Size, Sales Growth and Tax Aggressiveness - Aprida, Aprida; Hidayati, Wahyu Nurul (EAJ (Economic and Accounting Journal), 2023)
This study analyses the effect of Capital Intensity, Deferred Tax Expense, Company Size, and Sales Growth on Tax Aggressiveness. The independent variables used in this research are capital intensity, deferred tax expense, company size and sales growth. The dependent variable used is Tax Aggressiveness. The population of this study is non-cyclical sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The data source used in this study is secondary data in the form of published company financial reports. This study used a quantitative method with sampling carried out using a purposive sampling method. The number of companies sampled in this study was 10 (ten). Data processing uses E-Views 9 (nine). The results of this study show that Capital Intensity, Deferred Tax Expense, Company Size, and Sales Growth do not affect Tax Aggressiveness. The difference between this research and previous research is that the year of research in this study is the year used in the last year. Besides that, the sector studied in this study differs from previous studies.